The Variorum Edition of the Poetry of John Donne : The Divine Poems - Donne, John, 1572-1631 (Book collections on Project MUSE., 2020)
"Based on an exhaustive study of the manuscript and print history of Donne's poetry, this edition presents newly edited critical texts of the poems and a comprehensive digest of the critical-scholarly commentary on them from Donne's time forward. Textual introductions briefly locate the poems in the context of Donne's life or poetic development, outline the 17th-century textual history of the poems, and sketch the treatment of the text by modern editors. A detailed textual apparatus presents variants collated from many sources and traces the lines of textual transmission"--Provided by publisher.